Basic income: An early Icelandic experiment - Jóhannes Karlsson; Thórólfur Matthiasson (University of Iceland, Institute of Economic Studies (IoES), 2018)
Old age, sickness and/or physical and/or mental disability may limit the ability of an individual to generate enough income to cover basic cost of living. Most developed nations provide financial assistance for persons with limited ability to support themselves economically. In 1974, the Icelandic Parliament, headed by a left-wing government passed legislation providing a tax credit, payable to taxpayers under certain conditions. The tax allowance was applied firstly to settle the taxes and public levies owed by the taxpayer, with any amount remaining paid out to the individual. This system can be seen as a first, limited attempt at establishing a partial universal basic income of sorts. The lesson is that basic income, would need strong supporters if implemented, where the role of the government and/or the parliament would be mapped. Its supporters must be able to withstand the pressure from the social partners in the labour market because of the interactivity of the Social security system and the pension fund system which is not part of the fiscal system in Iceland. The conflict of interests becomes apparent.
Keywords: 330; basic income; Iceland; Grundeinkommen; Island